Disconnected Youth? - MacDonald, R. author. aut Link
VIII, 252 p. 1 illus.
Keywords: How do young people get by in hard times and hard places? Have they become a 'lost generation' disconnected from society's mainstream? Do popular ideas about social exclusion or a welfare dependent underclass really connect with the lived experiences of the so-called 'disaffected', 'disengaged' and 'difficult-to-reach'? Based on close-up research with young men and women from localities suffering social exclusion in extreme form, Disconnected Youth? will appeal to all those who are interested in understanding and tackling the problems of growing up in Britain's poor neighbourhoods.